Heterozygous familial hypercholesterolemia: prevalence and control rates. Issue 4 (4th July 2021) - Polychronopoulos, Georgios; Tzavelas, Marios; Tziomalos, Konstantinos
ABSTRACT: Introduction : Heterozygous familial hypercholesterolemia (heFH) is associated with a very high risk for cardiovascular events. Treatment with potent statins substantially reduces cardiovascular morbidity in these patients. Moreover, combination therapy with statins plus ezetimibe and/or proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors facilitates achievement of low-density lipoprotein cholesterol (LDL-C) targets in patients with heFH. However, heFH remains underdiagnosed and undertreated worldwide. Areas covered : In this review, we summarize current evidence on the prevalence and control rates of heFH. Accumulating data suggest that heFH is one of the most common hereditary metabolic disorders, affecting approximately 1 in every 300 individuals. However, only a small minority of patients with heFH achieve LDL-C targets, even in high-income countries and in subjects followed-up in specialized lipid clinics. Expert opinion : Given the underdiagnosis of heFH using cascade and opportunistic screening, wider, population-based screening strategies should be evaluated for their feasibility and cost-effectiveness if we aspire to timely diagnosis and therefore prevention of cardiovascular morbidity and mortality in this very high risk population. Overcoming inertia in uptitrating statin dose, adding ezetimibe and/or PCSK9 inhibitors along with more generous reimbursement for lipid-lowering agents in patients with heFH are essential for improving goal attainment rates.